Inhabited Pasts: Monuments, Authority, and People in Delhi, 1912–1970s. Issue 4 (19th September 2018) - Sutton, Deborah
Abstract : This article considers the relationship between the official, legislated claims of heritage conservation in India and the wide range of episodic and transitory inhabitations that have animated and transformed the monumental remains of the city, or rather cities, of Delhi. Delhi presents a spectrum of monumental structures that appear variously to either exist in splendid isolation from the rush of everyday urban life or to peek out amidst a palimpsest of unplanned, urban fabric. The repeated attempts of the state archaeological authorities to disambiguate heritage from the quotidian life of the city was frustrated by bureaucratic lapses, casual social occupations, and deliberate challenges. The monuments offered structural and spatial canvases for lives within the city, providing shelter, solitude, and the possibility of privacy, as well as devotional and commercial opportunity. The dominant comportment of the city's monuments during the twentieth century was a hybrid monumentality, in which the jealous, legislated custody of the state became anxious, ossified, and ineffectual. An acknowledgement and acceptance of the hybridity of Delhi's monuments offers an opportunity to reorient understandings of urban heritage.